Assessing old-age poverty with income and assets: Generational insights and policy directions - Seunghee Lee (Korea Development Institute (KDI), 2023)
Korea's old-age poverty rate, based solely on income, ranks among the highest in the OECD. While the rate drops slightly when assets are considered, it remains persistently high. There are marked disparities in poverty rates across different elderly birth cohorts, with older groups facing higher rates. A greater share of the low-income, low-asset segment also marks the observed inequality. To effectively address poverty among the elderly, policy efforts should prioritize support for the oldest members of this vulnerable low-income, low-asset segment. Concurrently, financial assistance for seniors in the low-income, high-asset group should be scaled back. A practical move toward this direction would be revising the eligibility criteria for the Basic Pension to include asset-inclusive pensionable earnings.
Keywords: 330